PENGARUH KEBAHAGIAAN DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KEPUASAN KERJA KARYAWAN STAR SQUARE MANADO - Anggilia Mamaahit (Jurnal Riset Multidisiplin Edukasi, 2025)
Property company PT Bhuwanatala Indah Permai Tbk (BIPP), through its subsidiary PT BIP Tridaya Propertindo, plans to acquire 70,000 shares worth IDR 70 billion from PT Artoda Karya Gemilang. Artoda is currently developing a commercial project in Manado, namely a commercial complex called Star Square, which includes a shopping center (mall). The aim of this research is to assess the impact of happiness and organizational citizenship behavior (OCB) on the job satisfaction of employees at Star Square Manado. The study employs a quantitative method with hypothesis testing using multiple linear regression, and the sample is selected through accidental sampling. Data collection is conducted through questionnaires. The results of the t-test or partial test indicate that happiness and OCB each have a significant influence on the job satisfaction of Star Square Manado employees. The conclusion drawn from this research emphasizes the importance for Star Square Manado to pay attention to happiness and OCB as determinants of employee job satisfaction. It is also recommended that the management of Star Square Manado consider the established targets.